Incidences of Calf Diarrhea and the Associated Risk Factors in Ivory Coast (2015-2017) (Revista de Ciências Agroveterinárias, 2020)
Diarrhea is the most important disease of neonatal calves, and it results in the greatest economic losses. A longitudinal observational study was conducted from September 2015 to October 2017. This study proposes to investigate the incidence of diarrhea in calves and their mortality rate so as to identify potential risk factors related to the occurrence of calf diarrhea on 372 farms in the regions of Abidjan, Bouake, Bondoukou, and Korhogo in Ivory Coast. Information on potential risk factors was collected based on personal observations from regular visits to the farms and from a survey conducted during the period of the study. A total of 2020 calves under the age of three months were selected. Only 347 (17.17%) of the 2020 calves showed signs of diarrhea. The overall mortality rate was 0.39%. Based on the survey, colostrum feeding, the calf’s age and sex, calf housing, seasonal variation, the calving period, environment conditions, the ignorance of herdsmen, and management systems were found to be the major risk factors for gastroenteritis in calves. Calves reared in an extensive system were less susceptible to neonatal diarrhea. The calf health and management issues found in this study can be resolved by creating awareness among farm owners and implementing better calf management practices and cattle vaccination programs.
Keywords: Diarrhea; Calf; Mortality; Risk factors; Ivory Coast